(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
In order to develop relatively small molecules as pharmacologically active molecules, a series of novel oxazolidinones having benzothiazinen and their derivatives were synthesized, and characterized by IR, 1H NMR and Mass spectral studies. Various substituted oxazolidinones benzothiazinen were prepared by simple reflux in the presence of acetonitrile. Treatment of these oxazolidinones benzothiazinen deravatives with methanesulfonyl gives its sulphonates derivatives on further treatment with sodium azide and tri phenyl phosphine in acetic anhydride to give its acetamide derivatives. Further the synthesized compounds were evaluated for antibacterial activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and antifungal activity against, Candida albicans and Aspergillus niger.